2012
DOI: 10.1186/1757-2215-5-36
|View full text |Cite
|
Sign up to set email alerts
|

Markers of stem cells in human ovarian granulosa cells: is there a clinical significance in ART?

Abstract: BackgroundThe purpose of the study was to determine the incidence of gene expression of Oct-4 and DAZL, which are typical markers for stem cells, in human granulosa cells during ovarian stimulation in women with normal FSH levels undergoing IVF or ICSI and to discover any clinical significance of such expression in ART.MethodsTwenty one women underwent ovulation induction for IVF or ICSI and ET with standard GnRH analogue-recombinant FSH protocol. Infertility causes were male and tubal factor. Cumulus–mature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 87 publications
(98 reference statements)
7
34
0
Order By: Relevance
“…Additionally, GCs were positive for various markers of mesenchymal stem cells: CD29, CD44, CD90, CD105, CD117, and CD166, but not for CD73 [41]. Another study by Varras et al [77] showed that OCT-4 gene was expressed in GCs of women included in the assisted reproduction program, namely in 48 % of the studied women; however, the expression of this gene was demonstrated only by real time-PCR methodology. They carefully analyzed if OCT-4 expression was related to female clinical parameters (i.e., age, BMI, duration and causes of infertility, previous assisted reproduction attempts, basal serum FSH and LH levels, serum levels of PRL, serum estradiol levels on the fifth day of rFSH administration and on the day of hCG administration, the total dose of rFSH, the duration of treatment, the type of assisted reproduction, the number of aspirated follicles etc.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, GCs were positive for various markers of mesenchymal stem cells: CD29, CD44, CD90, CD105, CD117, and CD166, but not for CD73 [41]. Another study by Varras et al [77] showed that OCT-4 gene was expressed in GCs of women included in the assisted reproduction program, namely in 48 % of the studied women; however, the expression of this gene was demonstrated only by real time-PCR methodology. They carefully analyzed if OCT-4 expression was related to female clinical parameters (i.e., age, BMI, duration and causes of infertility, previous assisted reproduction attempts, basal serum FSH and LH levels, serum levels of PRL, serum estradiol levels on the fifth day of rFSH administration and on the day of hCG administration, the total dose of rFSH, the duration of treatment, the type of assisted reproduction, the number of aspirated follicles etc.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
“…), but they did not find any correlation. Unlike Kossowska-Tomaszczuk et al [41] study in which GCs were pooled from various infertile women, Varras et al [77] analyzed the gene expression of GCs in each single patient with tubal factor of infertility or with infertile partner. Although the OCT-4 transcription factor is a solid marker of cell stemness, we need to be careful when selecting the appropriate primers.…”
Section: Expression Of Stem Cell Markers In Granulosa Cells From Follmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown in several publications that some GCs in the growing follicle are not fully differentiated and exhibit stem cell properties across mammals, i.e. : ovine, porcine and human GCs (28,29,38,49). Besides stem cell properties, GCs also present high telomerase activity and are capable of differentiation into cell types that are not present within ovaries.…”
Section: Nsn (Mii(nsn)) or Competent Metaphase Ii-derived Sn (Mii(sn)mentioning
confidence: 99%